Alpine Ski Coaches’ and Athletes’ Perceptions of Factors Influencing Adaptation to Stress in the Classroom and on the Slopes - Davis, Paul; Halvarsson, Anton; Lundström, Wictor; Lundqvist, Carolina (Frontiers in Psychology, 2019)
Research examining the student-athlete experience proposes a number of factors that can be both sources of stress and/or support. The dual career pathway offers a number of potential positive outcomes including psychological, social, and financial benefits; however, challenges including time management, fatigue, and restricted social activities are well documented. In consideration of the multidimensional student-athlete experience and the numerous factors that influence the complexity of potential stress, a mixed methods research study design was used in the study. First, data collected from surveys completed by 173 elite junior alpine skiers were analyzed to identify the degree to which athletes report experiencing stress associated with specific aspects pertaining to training, life, and organizational factors. These factors were then explored through semi-structured interviews with six coaches at the associated national elite sport schools. Taken collectively, athletes’ reports of psychophysiological training stress on the Multidimensional Training Distress Scale were low. Scores on the college student-athletes’ life stress scale revealed very low levels of general life stress; although the subscales associated with “performance demand” and “academic requirements” scored marginally higher. Scores on the Organizational Stressor Indicator for Sport Performers indicated low levels of organizational stress. The interviews with coaches elucidated the underlying factors potentially influencing athletes’ positive adaptations to stress as they reported programming a number of strategies to reduce negative outcomes. Coaches aimed to teach athletes self-awareness and regulation strategies through the use of the training diaries and ongoing communication to promote positive adaptation to stress. A number of coaches also worked with sport psychology consultants to optimize athletes’ training and study situations. Traditionally, research has noted high levels of stress in student-athletes due to co-occurring demands (school & sport); however, the data in the present study suggests that optimizing support mechanisms across domains can promote positive adaptations to potential sources of stress.